Combining individual Chlamydia trachomatis IgG antibodies MOMP, TARP, CPAF, OMP2, and HSP60 for tubal factor infertility prediction - van Ess, Eleanne F. (Am J Reprod Immunol, 2019)
PROBLEM: Tubal factor infertility (TFI) is a severe complication of genital Chlamydia trachomatis infections. In fertility workup, chlamydia antibody test (CAT) is used to predict TFI. The predictive value for TFI of most commonly used CAT is moderate. METHOD OF STUDY: A total of 183 infertile Dutch Caucasian women were included in this study. All underwent tubal patency testing (hysterosalpingography [HSG] or laparoscopy). Cases had TFI, and controls had no TFI (ie normal findings during HSG or laparoscopy). TFI was categorized based on severity (TFI 1‐TFI 4). This study investigated the predictive values of major outer membrane protein (MOMP), translocated actin‐recruiting phosphoprotein (TARP), chlamydial protease‐like activity factor (CPAF), heat shock protein‐60 (HSP60) and outer membrane protein 2 (OMP2) for TFI. A predictive algorithm is developed to detect TFI with a high certainty based on combinations of antibody titres. Serum was tested with the Mikrogen recomLine immunoblot and quantified with the recomScan. A greedy algorithm that explores all possible antibody combinations was developed. RESULTS: Significant differences in the distributions of antigen titres between cases and controls were observed for CPAF (P = 0.0021), HSP60 (P = 0.0061), MOMP (P = 0.0497) and OMP2 (P = 0.0016). Single antibodies could not discriminate between TFI and controls by themselves. The greedy algorithm performs better in specificity, positive predictive value (PPV), accuracy and clinical utility index than the original Mikrogen algorithm. CPAF combined with HSP60 identified 18.2% of TFI cases with 100% certainty. Most of the TFI 4 cases were identified with cut‐offs of CPAF > 10.7 or OMP2 > 3.9. CONCLUSION: This proof‐of‐principle study shows that combinations of antibodies in serum are predictive for TFI. A commercially available test can be adapted to predict TFI with a 100% specificity.